Pengembangan Media Scrapbook Pendidikan Kewarganegaraan Pada Materi Keberagaman Budaya Indonesia Kelas IV Sekolah Dasar - Aisyah; Kurnia Arda Januar Angelina Putri; Roni Setiawan (Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to develop scrapbook media in Civic Education subjects with a focus on the material of Indonesian cultural diversity for fourth grade elementary school students. The main problem in Civic Education learning is the lack of interesting and interactive learning media, so that students have difficulty in understanding the concept of cultural diversity. This study uses the Research and Development (R&D) method with the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study involved 25 fourth grade students of SDN 2 Bandung Baru. The research instruments were in the form of expert validation sheets, student response questionnaires, and learning outcome tests. The results showed that the developed scrapbook media received a very valid assessment from material experts (88.5%), media experts (90.2%), and education practitioners (87.8%). Student responses to the scrapbook media showed a very positive category with a percentage of 92.3%. The increase in student learning outcomes was also significant with an average pretest score of 68.4 increasing to 84.6 on the posttest. Scrapbook media has proven effective in   improving students' understanding of Indonesian cultural diversity and can be recommended as an alternative PKN learning media in elementary schools